MANUAL FOR IBADAH CAMP ORGANIZER A PART OF THE IIUM FLAGSHIP ENTITLED “GENDER DYSPHORIA” - Md Aris, Mohd Aznan; Draman, Samsul; Kamaruzaman, Nor Azam; Ibrahim, Muhammad; Md Isa, Muhammad Lokman; Mokhtar@Makhtar, Khairani Idah; J.A Ichwan, Solachudin; Lestari, Widya; Faisal, Ghasak Ghazi; Che' Man, Mohamad; Ab Rahman, Norny Syafinaz; Radeef Al-Ani, Ali Sabri; et al. (IIUM Press, 2022)
Maknyah or male-to-female transgender are those who transform their identity biologically from male to female through crossdressing and their lifestyle associated with homosexuality. Crossdressing and homosexuality are unlawful in accordance with Islamic practices. Often, these transgenders are associated with being sex workers in major hotspots such as in Federal Territory Kuala Lumpur, Selangor, Negeri Sembilan, Pulau Pinang, Pahang and Sarawak.1 It is estimated that the population size of sex workers in Malaysia in 2018 is 37,000 (22,000 Female Sex Workers and 15,000 Transgender Sex Workers). Despite the reducing number of transgender sex workers in Malaysia (as compared to previous Key Population Estimates in 2010), it is still a concern to Muslims and this trend needs to be relieved promptly.